Repetitive Deep TMS for Parkinson Disease: A 3-Month Double-Blind, Randomized Sham-Controlled Study. Issue 2 (March 2018) - Cohen, Oren S.; Rigbi, Amihai; Yahalom, Gilad; Warman-Alaluf, Naama; Nitsan, Zeev; Zangen, Abraham; Hassin-Baer, Sharon
Abstract : Purpose: To study the effects of a repetitive deep transcranial magnetic stimulation (rDTMS) in patients with Parkinson disease using the H5 coil for the low-frequency stimulation of the primary motor cortex, followed by the high-frequency rDTMS of the prefrontal cortex. Methods: The main outcome measures were the total and motor scores of the Unified Parkinson's Disease Rating Scale (UPDRS). Secondary measures included rating of depression and quantitative motor tasks. Results: Forty-eight patients were randomized 1:1 into real or sham rDTMS treatment arms. Analyses ( n = 42) of both UPDRS scores revealed a significant main effect for time between baseline and day 90 (end of treatment), indicating that there was an improvement of both scores over time in the whole sample. Although effects of treatment and time-by-treatment were insignificant, simple effects analysis of both measures was significant in the rDTMS group and reached a P -value of 0.06 in the sham group. The response rate was higher in patients with longer disease duration and higher motor UPDRS scores. Side effects were more common in the rDTMS group but were transient and tolerable. Conclusions: Although rDTMS treatment exhibited some motor improvements, we could not demonstrate an advantage for real treatment over sham. Further research is required to establish stimulation parameters that may induce potentially more beneficial outcomes, probably in patients with longer and more sever disease.